Lack of 5-lipoxygenase in intramembranous and endochondral 129Sv mice skeleton and intramembranous healing - Simionato, Gustavo Baroni [UNESP]; da Silva, Ana Claudia Rodrigues [UNESP]; Oliva, André Hergesel de [UNESP]; de Abreu Furquim, Elisa Mara [UNESP]; Couto, Maira Cristina Rondina; Shinohara, André Luis; Biguetti, Claudia Cristina; Matsumoto, Mariza Akemi [UNESP] (Elsevier, 2021)
Objective: To analyze the lack of 5-lipoxygenase (5LO) on dental socket healing and post-natal phenotype of intramembranous and endochondral bones. Design: Wild type (WT) 129/SvEv (n = 20) and 5LO knockout (5LOKO) (n = 20) male mice underwent tooth extraction of the upper right incisor and were euthanized after 7, 14, and 30 day time points for the evaluation of dental socket healing and histological phenotyping of intramembranous (IM) and endochondral (EC) bones. Microscopic analysis of alveolar sockets included histopathological description, histomorphometry, and immunohistochemistry for 5LO, cyclooxygenase 2 (COX2), and tartrate resistant acid phosphatase (TRAP). Results: Histological phenotyping revealed thicker cortical bone in EC bones (femur and vertebra) of 5LOKO mice compared to WTs, with no differences in collagenous content. Although dental socket healing was similarly observed in both groups, WT mice revealed increased numbers of COX-2+ and 5LO+ cells during bone maturing stage, with a decrease of TRAP+ cells at day 30. On the other hand, an increased quantity of fibroblasts was observed at day 7 in 5LOKO group, as well as increased inflammatory infiltrate and significantly decreased TRAP+ cells at final stages of alveolar socket healing in comparison to WTs. Conclusions: The lack of 5LO in 5LOKO mice resulted in thicker cortical of EC, but not of IM post natal bones. Furthermore, genetic deletion of 5LO in the 5LOKO mice directly affected the inflammatory response during socket healing, influencing initial and late phases of bone repair in a model of post-tooth extraction in 129Sv WT and 5LOKO mice.
Keywords: 5-lipoxygenase; Bone formation; Healing; Intramembranous bone; Mice